Pyritization of the coastal sediments in the Kelantan plains in the Malay Peninsula during the Holocene - Mohd Sufian Kang, Enio Kang; Jusop, Shamsuddin; Ishak, Che Fauziah; Mohd Hanif, Ahmad Husni (Science Publications, 2011)
Problem statement: For a number of geological reasons a proportion of the present coastal plains in the Malay Peninsula were inundated by seawater in the past when pyrite in some of the soils is believed to have been mineralized. Random survey of these sites showed a unique distribution and depth of pyritic layer in the soils along the coastal plains. A study was conducted in order to explain the mechanism of pyritization in the sediments of the present day coastal plains in Kelantan, Peninsular Malaysia. Approach: Soil surveys were conducted and soils were sampled and analyzed. Spatial distribution of the pyritic soils was used to construct an imaginary line to indicate the probable position of the shoreline when the sea level was at its highest. Results: Results of the study showed that soils containing pyrite occur sporadically in the plains. This pyrite occurs in the soils at varying depth; some soils have pyritic layer below 2 m from the surface (northern region), while others have pyrite in the surface horizon (southern region). Pyrite was formed by the reaction of ferrous and sulfide ions which were respectively reduced from ferric ions (sediments) and sulfate (seawater) ions, respectively. In the middle of the study area, pyritic layer overlain by peaty materials were observed. Conclusion: The presence of pyrite in the soils can be used as an evidence for sea level rise in the area during the Holocene. This pyrite is assumed to have been formed about 6,000 years BP when the sea level rose 3-5 m above the present. Its oxidation has caused untold damage to the productivity of the paddy soils in the area.